Technologies, feasibility, and management strategies for on-board multi-source energy networks - Ahmed, Sanjana; Castellazzi, Alberto; Williams, Arthur (2016)
The paper discusses the feasibility of installing renewable energy generation technologies on sea-going transport, taking into account the additional weight and power consumption. This study in based on the power management of a 26,198 tonne commercial chemical tanker. The management system would aim at reducing the number of generators as well as the power required from burning fossil fuels. After a process of elimination of potential technologies based on feasibility of the project and shipboard application, the work is focused towards photovoltaic and wind energy generation in combination with fossil fueled engines and Li-ion battery storage covering the higher energy density needs, and the intermittent nature of renewables. The network architecture is optimized in order to have the highest efficiency, and reduced system weight. The results show that successful management of the system can lead to reduction in generator requirement, as well as fuel consumption and energy despite the weight of the extra installation.